Multimedia Development E-Flashcard in Class XI Vocational School Business Economics Subjects - Ananda, Rahma; Anugrah, Septriyan; Kurnia Yusri, Meldi Ade; Masnur, Alkadri (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Along with advances in technology, the use of learning media has become crucial, especially in Vocational High Schools (SMK). This research aims to develop multimedia e-flashcard as a means of learning Business Economics. Based on theory Edgar dale Regarding concrete experiences, learning that involves real activities is proven to be more effective in increasing students' understanding. The main focus of this research is to describe the product development and evaluation process to ensure its validity, practicality and effectiveness in improving student learning outcomes in class XI vocational school business economics subjects. The method used is a development model Borg and gall, which makes it possible to test and improve the product. The validation test results show that the average material validation score reached 5.00, including the